Behavior as the Basis of Stage Art - Shavkat Shukhratovich , Rasulov (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses how behavior is the foundation of performing arts. Recommendations for stage behavior are given. K.S. Stanislavsky’s descriptions of behavior are given in examples of proof of thought.